In vitro degradability test on rice bran containing Tithonia diversifolia (HEMSL.) A. Gray and kelor (Moringa oleifera, LAMK) leaves - ., Firsoni; Fortuna, Conny; Lisanti, Elsa (Indonesian Animal Sciences Society, 2010)
A research was done to investigate the advantages of Tithonia diversifolia (Hemsl.) A. Gray and Moringa oleifera LamkÂ leaves as protein source in ruminant concentrate on in-vitro rumen metabolism. Randomized Block Design with 4 treatments and 5 replications was applied in this experiment. The treatments were: A = Tithonia diversifolia (TD) 75% + Rice Bran (DD) 25%: B = TD (56.25%) + Moringa oleifera (MO) 18.75% + DD 25%; C = TD 37.50%) + MO 37.50% + DD 25%; D = TD 18.75% + MO 56.25% + DD 25%. Samples were weighted 375 Â± 5 mg, placed into syringe glass 100 ml, 30 ml rumen liquor with bicarbonat buffer media was added and incubated in 390C for 48 hours. Parameters measured were gas production after 0, 2, 4, 6, 12, 24, and 48 hours incubation, degradability of organic matter (DBK) and dry matter (DBO), NH3, total VFA concentration, and microbe biomass production (mg) after 48 hours incubation. Results showed that Moringa oleifera replaced some Tithonia diversifolia in concentrate could improve gas production, total VFA concentration, DBK and DBO significantly (P < 0.05). The highest gas production was obtained from treatment D (52.98 ml/375 mg DM) and the lowest was from treatment A (41,02 ml/375 mg DM). The highest VFA total was produced by treatment D (88.20 mM) and the lowest was from treatment A (78.86 mM). The highest DBK dan DBO were obtained from treatment D (73.74 and 73.32%) and the lowest was from treatment A (68.77 and 67.54%). Treatment D produced the highest NH3 and microbial biomass (38.09 mg/100 ml and 89.50 mg), the lowest was obtained from treatment A (35.84 mg/100 ml and 84.66 mg). Key Words: Tithonia diversifolia (Hemsl.) A. Gray, Moringa oleifera Lamk, Protein, Rive Bran,Â In Vitro